Higher serum uric acid level is inversely associated with renal function assessed by cystatin C in a Japanese general population without chronic kidney disease: the KOBE study - Sachimi Kubo; Yoko Nishida; Yoshimi Kubota; Aya Higashiyama; Daisuke Sugiyama; Takumi Hirata; Naomi Miyamatsu; Ayumi Tanabe; Aya Hirata; Yukako Tatsumi; Aya Kadota; Kazuyo Kuwabara; et al. (BMC Nephrology, 2019)
Abstract Background Although several epidemiological studies have suggested that high serum uric acid (SUA) levels are related to a decline in kidney function, only a few studies have investigated using cystatin C to calculate estimated glomerular filtration rate (eGFR). We aimed to clarify the relationship between SUA levels and kidney function assessed by cystatin C in a Japanese general community population without chronic kidney disease (CKD). Methods We conducted a community-based cross-sectional study that included 1086 healthy participants, aged 40–74 years, without CKD and not undergoing treatment of hyperuricemia, who had participated in the baseline survey of the Kobe Orthopedic and Biomedical Epidemiological (KOBE) study. The preconditions for participation in this study were no past histories of cardiovascular disease or cancer, and not undergoing treatment for diabetes, hypertension, or dyslipidemia. We classified the participants into quartiles stratified by sex according to their SUA level and then examined the relationship with eGFR. The odds ratios for having a low eGFR, defined as the lowest quartile of eGFR (i.e., ≤78.4 mL/min/1. 73m2) was estimated according to SUA quartiles (men, Q1 ≤ 5.0, Q2 5.1–5.9, Q3 6.0–6.6, and Q4 ≥ 6.7; women, Q1 ≤ 3.8, Q2 3.9–4.3, Q3 4.4–4.9, and Q4 ≥ 5.0 mg/dL) after adjustment for age, body mass index, systolic blood pressure, HbA1c, high and low density lipoprotein cholesterol, and smoking and drinking habits. The adjusted mean of each quartile was also calculated. Results Multivariable-adjusted means of eGFR showed a graded decrease in higher SUA quartiles (men, Q1 90.5, Q2 88.0, Q3 83.5, and Q4 82.0; women, Q1 95.7, Q2 91.3, Q3 89.2, and Q4 86.7). In addition, the multivariable-adjusted odds ratios for having a lower eGFR (95% confidence interval) for each SUA quartile compared with Q1 was Q2 2.29 (0.98, 5.35), Q3 4.94 (2.04, 11.97), and Q4 8.01 (3.20, 20.04) for men, and was Q2 2.20 (1.12, 4.32), Q3 2.68 (1.39, 5.20), and Q4 4.96 (2.62, 9.41) for women. Conclusions There was a graded inverse relationship between mild elevations in SUA levels and eGFR assessed by cystatin C in an apparently healthy Japanese population without CKD. This association was similar in both men and women.